Os saberes psicológicos na Escola Normal de Ouro Preto entre 1890 a 1930 - Deolinda Armani Turci (2014)
The objective of this research was to perform a historiographical study of the psychological knowledge that circulated in Ouro Preto Normal School in the period stretching from 1890 to 1930. The schools were Brazilian Standard teacher training space since the mid-nineteenth century and the School Normal Ouro Preto in Minas Gerais was the first school of teacher education in the state. For the work we use the theoretical framework of the history of psychology and historiography and as a method used document analysis, by reading specific literature of the field and location procedures, recovery, selection, arrangement and analysis of primary sources. The consulted documents such as evidence of the students of the materials programs, mining educational legislation and Periodicals Journal of Teaching and Official Journal Minas Gerais, took center stage in the current analysis. The results showed that from the 1880s, in Ouro Preto Normal School, with the modification and expansion of its curriculum the psychological knowledge were present in the field endorsing the training of new teachers. Throughout the twentieth century until 1930, psychology was becoming more and more significant place in teacher training and education in Minas Gerais. We believe that the results obtained from the research contribute to the understanding of the history of psychology in Minas Gerais and in particular in Brazil in general.